2000
DOI: 10.1038/sj.jea.7500085
|View full text |Cite
|
Sign up to set email alerts
|

Manganese exposures in Toronto during use of the gasoline additive, methylcyclopentadienyl manganese tricarbonyl

Abstract: A year -long population -weighted study of personal exposures to particulate matter ( PM 2.5 ) was conducted in Toronto while the manganese -containing additive, methylcyclopentadienyl manganese tricarbonyl ( MMT ) , was present in gasoline at an average level of 11.9 mg Mn / l, which was higher than the maximum of 8.3 mg Mn / l allowed in the U.S. In this study, 925 three -day personal samples of PM 2.5 ( air concentration of aerosol with an aerodynamic diameter of less than 2.5 m ) were collected, along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…For Mn, the ''time spent metal working / welding / soldering'' and ''time in an enclosed workshop'' appeared as the strongest correlates. In the Toronto nonoccupationally exposed subpopulation, the strongest predictor of Mn 2.5 personal exposure was the amount of time traveling by subway ( Crump, 2000 ). Indianapolis, of course, does not have a subway system.…”
Section: Interelement Correlationsmentioning
confidence: 99%
“…For Mn, the ''time spent metal working / welding / soldering'' and ''time in an enclosed workshop'' appeared as the strongest correlates. In the Toronto nonoccupationally exposed subpopulation, the strongest predictor of Mn 2.5 personal exposure was the amount of time traveling by subway ( Crump, 2000 ). Indianapolis, of course, does not have a subway system.…”
Section: Interelement Correlationsmentioning
confidence: 99%
“…Pfeifer et al (1999) reported that there was more manganese in London commuters' blood than in taxi drivers' blood. Crump reported that time spent in Toronto subways was the best predictor of manganese in personal blood samples in his study (Crump, 2000). Chillrud et al (2004Chillrud et al ( , 2005 studied personal exposures to iron, manganese, and chromium dust among students and workers in New York City (NYC) and found that the NYC subway is the dominant source of these exposures.…”
Section: Adverse Health Effectsmentioning
confidence: 99%
“…Studies of atmospheric ambient aerosols in the United States, United Kingdom, and Canada have reported total manganese air concentrations in the range of <1 to 50 ng m −3 (Allen et al 2001;Crump 2000;Kidwell and Ondov 2004). Ambient atmospheric manganese can be attributed both natural (e.g., resuspended soil) and anthropogenic (e.g., welding, fungicides, batteries, and steel production) sources (Mergler and Baldwin 1997).…”
Section: Introductionmentioning
confidence: 99%